The treatment of elinical mastitis with alfasilin in dairy cattle - Hüseyin DEVECİ; Hüseyin TİMURKAN; Celal ÖZCAN; A. Mükremin APAYDIN (Eurasian Journal of Veterinary Sciences)
In this, study, the effectiveness of Aliasilin ( =ampicillin soduim) in treatment of elinical mastitis was investigated in dairy eattle. Fifty cows from different races were usedin the study. One hundred fifty four infected mammary quarters were treated with Alfasilin; According to the results of the ba.cteriological examinations, the first group had 25 cases which were found to be in sensitiveness of first or cond degree to Atnpicillin. Second group included 32 cases in which hacteriological examination was not done. Forty to fifty milliter of Aifasilin solution which contained 2.5 gram Aifasilin was injected in to each infected mammary quarter by teat canal. Also, 2.5 g Aifasilin was injected intramuscularly every day. The therapy lasted for five days from evening to evening, periodically. Milk samples obtained five to six days after the traetment were controlled by CMT (California Mastitis Test) and bacteriological examinations to determine the effecti veness of the treatment. The recovery ra tes of elinical masti tis were found as 67.74% in first anel second groups, respectivelly. As the results of the experiment, Aifasilin was found to be an effective antibiotic in the treatment of elinical mastitis.